Study Kualitatif Faktor Penyebab Kesepian Emosional pada Lansia - Nefa Restiani; Uus Husni Mahmud; Riza Arisanty Latifah (Universitas Faletehan, 2025)
Loneliness is often experienced by elderly living in nursing homes since they do not receive support from family members. This study aimed to analyze the factors causing emotional loneliness in the elderly. This study used a qualitative approach of phenomenological study and involved 4 participants who were selected using purposive sampling techniques. The research instruments used to collect data included mobile phones, pens, books, interview guides, and checklists compiled based on the UCLA Loneliness Scale Version 3. The data were analyzed using description, data reduction, essence, intentionality, triangulation as data validity and using Open Code software. The results of the thematic analysis obtained four main themes, namely: (1) lack of emotional support from the family for the elderly in nursing homes, (2) emotional adaptation of the elderly to the changes of residence, (3) no partner figure who provides affection, and (4) the elderly's perspective on social relationships with people in nursing homes. The results of the study indicated that the elderly have lack of family support which leads to the emotional loneliness. The results of this study were expected to provide additional information for developing education on the importance of family support and preventing loneliness in the elderly.